Acute ethanol intoxication induces preferred loss of presynaptic boutons devoid of mitochondria in vivo - Protzmann, Jil; Jaiswal, Astha; Rohr, Karl; Kuner, Thomas; Cambridge, Sidney; Knabbe, Johannes (bioRxiv beta, 2019)
Acute alcohol intoxication is frequently observed in modern societies and carries a vast burden, ranging from traffic accidents to transient memory loss. Despite years of intense research, the effects of acute ethanol intoxication on brain function remain incompletely understood. Here, we studied the effect of acute ethanol intoxication on axonal organelle trafficking and presynaptic structure using in vivo two photon microscopy in anesthetized mice. After a single intraperitoneal injection of ethanol, inducing a blood alcohol concentration of roughly 250 mg/dl, the axonal mitochondrial mobility was doubled while dense core vesicle mobility remained unaffected. Simultaneously imaging mitochondria and presynaptic boutons revealed that unoccupied presynaptic boutons perished more frequently after ethanol exposure, while boutons stably occupied with mitochondria mostly persisted. Our results define a novel mechanism of ethanol action and may explain difficulties in permanently storing new memories after episodes of intense ethanol consumption with a loss of synapses.
Gesehen am 11.02.2021